Biodegradable pH-responsive colourimetric indicators for smart packaging application - Khrystoslavenko, Olga; Sikandar, M. Usman (International Conference “Environmental Engineering”, 2026)
Increasing interest in more sustainable and intelligent smart packaging has promoted the use of organic dyes as simple freshness indicators. In this research, two ideas were applied: first, the use of plant-based, sensitive pigments for spoilage detection, and second, comparing biodegradable indicators with synthetic ones for packaging purposes. At the same time, the transition to biodegradable insulation and packaging materials is becoming increasingly important, especially for the food sectors that rely on temperature-controlled transport. Conventional synthetic pH indicators as phenolphthalein and bromothymol, are difficult to recycle and cause long-term environmental waste, while novel biobased materials manufactured from plant fibers can provide similar thermal insulation with substantially lower environmental effect. Red cabbage anthocyanins and turmeric curcumin natural indicators were extracted and applied onto filter-paper absorbents, which then described the substance’s acidity, neutrality, and basicity (or alkalinity). The absorbents showed clear, easily observable color transitions – anthocyanin changed from red to green-blue, while curcumin changed from yellow to a darker reddish- brown under alkaline conditions. These quick laboratory tests confirm that such natural indicators can function as cost-effective visual sensors for freshness monitoring. The findings demonstrate distinct differences across the indicators: curcumin responds weakly in basic conditions, bromothymol blue shows limited color changes around neutral to slightly alkaline pH (7–8), and phenolphthalein only reacts in extremely alkaline conditions (pH 9–10). When these biodegradable materials are combined with printed indicators using screen printing, extrusion, or additive manufacturing, the packaging can actively signal early spoilage or temperature-related changes.